Comparison of the Effectiveness of the Chemosurgery and Cryosurgery for the Treatment of Patients with Condyloma Acuminatum at Dr. Moewardi Hospital, Surakarta - Mawardi, Prasetyadi; Febrianto, Bobby; Yuliarto, Danu (Indonesian Journal of Medicine, 2021)
Background: Condyloma acuminatum (CA) is one of the most common sexually transmitted infections. Several therapeutic modalities that can be used are chemosurgery with trichloroacetic acid and cryosurgery with liquid nitrogen. Recurrence in CA often occurs, so selecting the right therapeutic modality and eliminating the lesion also prevents recurrence. This study aimed to compare the effectiveness of chemosurgery and cryosurgery therapy in patients with CA who are treated at Dr. Moewardi Hospital, Surakarta.Subjects and Method: A retrospective cross-sectional study was conducted at the Dermatology and Venereology Polyclinic, Dr. Moewardi Hospital, Surakarta, from January 1, 2018, to December 31, 2020. The study subjects were 78 patients diagnosed with CA based on ICD-10 criteria, while chemosurgery and cryosurgery procedures were based on ICD-9. The dependent variable was healing time in weeks. The independent variables were chemosurgery and cryosurgery therapy. The data came from the patient's medical record. Data were analyzed using an independent t-test.Results: Based on univariate analysis, most patients were male (67.9%), and the age group was 20-29 years (51.28%). Most of the CA patients work as private employees (46.15%). The most sexual orientation was heterosexual (53.8%), the most common site of lesions was genital (47.4%), and 52.6% were coinfected with HIV. Most CA patients received chemosurgery (70.5%). Bivariate analysis showed that chemosurgery therapy provided faster clinical improvement (Mean= 23.34; SD= 26.45) than cryosurgery therapy (Mean= 28.69; SD= 19.84), and the difference was statistically significant (p= 0.037).Conclusion: Treatment of CA using chemosurgery provides clinical improvement faster than cryosurgery, so that faster treatment time can reduce treatment costs and improve the patient's quality of life.Keywords: chemosurgery, cryosurgery, HPV, condyloma acuminatumCorrespondence: Prasetyadi Mawardi. Department of Dermatology and Venereology, Faculty of Medicine of Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia. Email: prasetyadimawardi@gmail.com/ prasetyadi_m@staff.uns.ac.id. Mobile: +6281229750211.Indonesian Journal of Medicine (2021), 06(03): 290-297https://doi.org/10.26911/theijmed.2021.06.03.06